The paradoxical consequences of choice: Often good for the individual, perhaps less so for society? - MADAN, Shilpa (Institutional Knowledge at Singapore Management University, 2020)
The proliferation of products and services, together with the rise of social media, affords people the opportunity to make more choices than ever before. However, the requirement to think in terms of choice, or to use a choice mind-set, may have powerful but unexamined consequences for judgment and decision making, both for the chooser and for others. A choice mind-set leads people to engage in cognitive processes of discrimination and separation, to emphasize personal freedom and independent agency, and to focus on themselves rather than others. Reviewing research from social psychology, legal studies, health and nutrition, and consumer behavior, we found evidence that although a choice mind-set may have positive consequences for the individual, the accumulated outcome of thinking in terms of individual choice may have detrimental outcomes for society. Given the prevalence of choice in all domains of life, more research examining the full range of the consequences of choice is urgently needed.